Extreme red shifted SERS nanotags. Issue 4 (2nd February 2015) - Bedics, Matthew A.; Kearns, Hayleigh; Cox, Jordan M.; Mabbott, Sam; Ali, Fatima; Shand, Neil C.; Faulds, Karen; Benedict, Jason B.; Graham, Duncan; Detty, Michael R.
Abstract : Extreme red-shifted nanotags have been developed and they provide effective SERS with picomolar detection limits when excited at 1280 nm. Abstract : Surfaced enhanced Raman scattering (SERS) nanotags operating with 1280 nm excitation were constructed from reporter molecules selected from a library of 14 chalcogenopyrylium dyes containing phenyl, 2-thienyl, and 2-selenophenyl substituents and a surface of hollow gold nanoshells (HGNs). These 1280 SERS nanotags are unique as they have multiple chalcogen atoms available which allow them to adsorb strongly onto the gold surface of the HGN thus producing exceptional SERS signals at this long excitation wavelength. Picomolar limits of detection (LOD) were observed and individual reporters of the library were identified by principal component analysis and classified according to their unique structure and SERS spectra.